Diagnosis and Treatment of Bronchopulmonary Lophomoniasis in a Patient with Persistent Granuloma: A Case Report - Antonio Mier-Briseño; Eloísa Ramírez-Alanís; Miguel Armando Benavides-Huerto; Francisco Alejandro Lagunas-Rangel (Reports)
Background and Clinical Significance: Lophomonas is a multiflagellate anaerobic protozoan that usually inhabits the intestines of insects, mainly cockroaches. However, bronchopulmonary infections caused by this parasite have been increasingly reported worldwide in recent decades. We provide important information for the diagnosis of this disease, which often goes undetected and frequently leads to misdiagnosis and inadequate treatment. It is noteworthy that this is the third case reported in Mexico. Case Presentation: A 37-year-old male patient was hospitalized several times for pneumonia with a persistent granuloma in the right bronchial lobe. After extensive testing, the patient was diagnosed with bronchopulmonary lophomoniasis and successfully treated with metronidazole. Conclusions: Clinicians worldwide should be aware of the existence of lophomoniasis, especially in low-income regions with poor sanitation and high insect exposure. This parasitic infection, although rare, may be underestimated due to its nonspecific respiratory symptoms, which may mimic other infections.